Eksistensi Perkawinan Prespektif Fiqh - Abdul Hafidz Miftahuddin (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2022)
Marriage is considered a blessing and a gift from Allah, through which individuals can continue their lineage and fulfill the Sunnah (teachings) of the Prophet. However, in order to enter into a valid marriage, certain conditions and pillars must be fulfilled according to Islamic law. These include: the presence of a prospective husband and wife, the presence of a guardian for the woman, two just witnesses, and the recitation of the marriage contract (ijab and qabul). The requirements include: the woman being permissible for marriage, the presence of witnesses during the marriage contract, and mutual agreement between the two parties. These are the essential elements that should be understood when it comes to marriage.